NIKLAS LUHMANN, OBSERVING SYSTEMS AND SOCIAL CRITIQUE - Salem, A. (Sociologija. Mintis ir veiksmas, 2015)
This article on the theories of the German sociologist Niklas Luhmann starts with a discussion of the formal codes that give what he calls communication systems their boundaries and coherence. It continues with an account of how these differentiating, observing systems can be seen to operate independently of human intervention, leading to a split between active, conscious human action and impersonal communication systems operating under their own logic, and more specifically to a split between conscious critique and social change. Throughout it is argued that observing and observed, reference and self-reference, and seeing and blindness, are all inseparably linked, raising serious questions about the status and function of social critique as conventionally understood.
Keywords: communications theory; second-order cybernetics; social change; social critique; social theory